The jagati with two projected niches on the south and north sides - Temples of India Project Team (Jio Institute, 2024)
Debris from the original temple was salvaged when the current temple was reconstructed in the 1940s. These have been assembled in parts to form the jagati (raised platform). However, it is not known where they were located in the original temple or if they came from multiple structures. Instead of the traditional shikhara, the temple was reconstructed with domes by the Archaeology Department of the erstwhile Jaipur State in the 1940s. The jagati has two projected niches on the south and north sides and a single projected niche on the west side. The dome pedestal and the domes on top of the mandapa (pillared hall) and the garbhagriha (sanctum) are made of concrete instead of stone, which is used in the rest of the temple structure. The open space surrounding the jagati is the pradakshina path (circumambulation path) on the adhisthana.